2016
DOI: 10.1016/j.livsci.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crude glycerine in supplement on the intake, rumen fermentation, and microbial profile of Nellore steers grazing tropical grass

Abstract: a b s t r a c tThe objective of this study was to evaluate the effect of crude glycerine (CG) inclusion in feed supplement (0, 70, 140, 210 and 280 g/kg DM basis of supplement) on the forage intake and digestibility, ruminal fermentation parameters, kinetics of fibre degradation, and rumen microbial profile of Nellore steers grazing on tropical grass. Ten ruminally cannulated Nellore steers [490 kg 7 47 body weight (BW)] were used in a replicated 5 Â 5 Latin square design with 14-d periods. Steers were indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Methane concentration was inhibited by 39.65% when 21% crude glycerin was included in TMR, compared to the TMR group with 0% crude glycerin. Regarding the influence of crude glycerin on in vitro CH 4 synthesis, Vito et al [21] indicated that concentration of CH 4 could be reduced with glycerin addition because of the adverse influence of glycerin on methanogen populatios. Vito et al [21] also suggested that supplementation of 28% of crude glycerin in Nellore steers grazing on tropical grass reduced methanogen population by 55.93% compared to the control group.…”
Section: In Vitro Rumen Parameters and Ch 4 Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Methane concentration was inhibited by 39.65% when 21% crude glycerin was included in TMR, compared to the TMR group with 0% crude glycerin. Regarding the influence of crude glycerin on in vitro CH 4 synthesis, Vito et al [21] indicated that concentration of CH 4 could be reduced with glycerin addition because of the adverse influence of glycerin on methanogen populatios. Vito et al [21] also suggested that supplementation of 28% of crude glycerin in Nellore steers grazing on tropical grass reduced methanogen population by 55.93% compared to the control group.…”
Section: In Vitro Rumen Parameters and Ch 4 Concentrationmentioning
confidence: 99%
“…Regarding the influence of crude glycerin on in vitro CH 4 synthesis, Vito et al [21] indicated that concentration of CH 4 could be reduced with glycerin addition because of the adverse influence of glycerin on methanogen populatios. Vito et al [21] also suggested that supplementation of 28% of crude glycerin in Nellore steers grazing on tropical grass reduced methanogen population by 55.93% compared to the control group. This might occur because the crude glycerin can modify the cell membrane permeability of methanogens, thus inhibiting the CH 4 production.…”
Section: In Vitro Rumen Parameters and Ch 4 Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental studies under similar conditions in Nellore cattle grazing quantified F . succinogenes by real time PCR showed that, even with low abundance in the rumen microbiota (<5%), these bacteria are important for forage degradation (San Vito et al ., 2016;Carvalho et al ., 2017;Neto et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, glycerin has the potential to be used as a sustainable alternative to replace corn as energy source in beef cattle finishing diets. Previous in vitro [ 3 , 8 ] and in vivo [ 9 , 10 ] studies have reported positive effects on ruminal fermentation when glycerin was included in beef cattle finishing diets. However, there is still controversy regarding the effects of glycerin on total gas production (GP) and enteric CH 4 production [ 11 ], NDF digestibility [ 2 ], the recommended levels of glycerin inclusion in beef cattle finishing diets [ 9 , 10 ], and its impact on ruminal fermentation of high fiber feeds [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%